Integration of the Adiwiyata Program in Social Sciences Learning as a Means of Strengthening Environmental Awareness at SMP Negeri 1 Karanganom - Tamara Devi Dhiyaulhaq; Sariyatun Sariyatun (Universitas Islam Negeri Sumatera Utara, 2026)
This study aims to analyze the integration of the Adiwiyata Program into Social Studies (IPS) learning as an effort to strengthen students' environmental awareness at SMP Negeri 1 Karanganom. This research is motivated by the importance of developing environmentally conscious character in students through learning integrated with environmental issues. The study used a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The research informants consisted of the principal, social studies teachers, the Adiwiyata coordinator, and students of SMP Negeri 1 Karanganom. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, with validity testing using source and technique triangulation. The results show that the integration of the Adiwiyata Program into Social Studies learning has been carried out through lesson planning, implementation of teaching and learning activities, and the instilling of environmentally conscious behavior in schools. Teachers integrated environmental values into the Social Studies material through contextual learning activities. The program has resulted in increased students' environmental awareness, although several obstacles remain, such as differences in students' levels of understanding and limited supporting facilities. Thus, the integration of the Adiwiyata Program into Social Studies learning contributes to fostering students' environmental awareness.